Efficacy of inactivated pasteurella multocida against the bacterial infections in broiler chickens - Koh, Sien Ling (2016)
Pasteurella multocida is the causative agent of fowl cholera in chickens. It causes economic losses to the poultry industry associated with high morbidity and mortality. The objective of this study was to determine the efficacy of inactivated P. multocida either as single or combination of serogroup A and D against the bacterial infection in broiler chickens. Eighty-four, day-old boiler chicken were separated equally into seven groups. On Day 1, chickens from groups 1 and 4 were inoculated with serogroup A, groups 2 and 5 with serogroup D while groups 3 and 6 with combination serogroup A and D. All the chickens were inoculated subcutaneously with 0.1mL of 1X1011 cfu/mL of inactivated P. multocida, except group 7 as control group. On Day 14, booster was given to groups 4, 5 and 6. On Day 28, all the chickens were divided into three groups namely non-challenge and challenge either via intramuscular or intranasal route. The study showed that one chicken each from group 1 and 7 dead at day 1 and 2 post challenge, respectively. At day 8 post challenge, all the chickens were scarified. P. multocida was isolated from the dead chicken in group 1 and 7. P. multocida was not isolated from all the other chickens scarified at day 8 post challenge. Gross lesions for the dead chickens reveled generalized congestion in the liver and kidneys while no significant gross lesion seen in sacrificed chickens. Histopathology findings for the dead chickens reveled severe congestion with severe necrosis and degeneration of hepatocytes. Severe pneumonia and severe congestion and necrosis of lung parenchyma were also recorded. In contrast, mild hepatitis with mild necrosis and degeneration of hepatocytes and mild pneumonia with mild congestion, degeneration and necrosis at the lung parenchyma were recorded in all the scarified chickens in all group. In conclusion, inactivated P. multocida combination of serogroup A and D could provide better protection against P. multocida serogroup A infection when compared to the single serogroup A or D.